Design and Analysis of Crankshaft Using Topology Optimization in ANSYS: Design and Analysis of Crankshaft Using Topology Optimization in ANSYS: A Study on Internal Combustion Engine (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The crankshaft is an important component of an engine. Crankshaft is one of the critical components for the effective and precise working of the internal combustion engine. A crankshaft can be called as the heart of any I.C. engine since it is the first recipient of the power generated by the engine. Its main function is to convert the oscillating motion of the connecting rod into rotary motion of the flywheel. The main function of a camshaft is to convert rotary motion of the crankshaft into vertically reciprocating motion of the valves required to open and close the intake and exhaust valves of engine cylinders, with the assistance of cams located on it and an intermediate mechanism. This paper presents the design connecting rod of internal combustion engine using the topology optimization. This paper 1 basic model and 3 implement model is proposed. The crankshaft model 3D geometry is created by using CATIA V5 and then it is import in ANSYS 19.0. and check all the result in three different load case 22624N, 32624N and 42624N.